Zeolite materials with Ni and Co: synthesis and catalytic potential in the selective hydrogenation of citral - Inocente Rodríguez-Iznaga; Yailen Costa Marrero; Tania Farias Piñeira; Céline Fontaine; Lexane Paget; Beatriz Concepción Rosabal; Arbelio Penton Madrigal; Vitalii Petranovskii; Gwendoline Lafaye (Beilstein Journal of Nanotechnology)
Zeolitic materials incorporating mono- and bimetallic systems of nickel and cobalt were obtained from natural zeolite modified with Ni2+ and Co2+ chloride solutions through traditional ion exchange (IE) and impregnation (Imp) processes. Special attention was given to analyzing the cationic and anionic composition of the resulting materials. The catalytic potential was evaluated in the selective hydrogenation of citral, focused on the formation of unsaturated alcohols. The IE process replaced mainly Ca2+ and Na+ with Ni2+ and Co2+ cations in the zeolite phases (clinoptilolite and mordenite mix), while Imp resulted in higher metal content (2.0–2.7%) but retained significant amounts of chloride (1.9–3.8%), as confirmed by XRD and temperature-programmed reduction. The materials prepared by IE had negligible chloride content (0.02–0.07%), and their specific surface areas (138–146 m2/g) were greater than those of the materials obtained by Imp (54–67 m2/g). The bimetallic systems exhibited enhanced reducibility of the Co2+ and Ni2+ isolated cations, attributed to synergistic interactions that weakened the cation–framework binding. Catalytic activity tests showed that nickel species were primarily responsible for citronellal formation. Among all materials, the bimetallic CoNiIE catalyst, prepared by IE, was the only one to produce unsaturated alcohols, suggesting that synergistic Ni–Co interactions played a role in their formation.